2020
DOI: 10.1136/bmjopen-2020-037243
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for an economic analysis of the randomised controlled trial of Improving the Well-being of people with Opioid Treated CHronic pain: I-WOTCH Study

Abstract: IntroductionOver the last two decades, the use of opioids for the treatment of chronic pain in England has steadily increased despite lack of evidence of both long-term effectiveness in pain relief and significant, well-documented physical and mental adverse events. Guidelines recommend tapering when harms outweigh benefits, but the addictive nature of opioids hinders simple dose-reduction strategies. Improving the Well-being of people with Opioid Treated CHronic pain (I-WOTCH) trial tests a multicomponent sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This review demonstrates the need for more high-quality research on opioid reduction strategies for patients with CNCP on LTOT. The fact that multiple research protocols for future research in this field were identified while scanning abstract and title [34][35][36][37] can be seen as a step in the right direction. These upcoming studies should build on lessons learned.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…This review demonstrates the need for more high-quality research on opioid reduction strategies for patients with CNCP on LTOT. The fact that multiple research protocols for future research in this field were identified while scanning abstract and title [34][35][36][37] can be seen as a step in the right direction. These upcoming studies should build on lessons learned.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…To explore the decision uncertainty associated with the cost-effectiveness of iFraP to enhance bisphosphonate adherence we will conduct a VoI analysis. An electronic search of trial-based economic evaluation of digital health interventions study protocols identified only three study protocols and neither of these included a trial based VoI analysis [42][43][44] . No VoI analysis was found when searching the published literature for protocols of cost-effectiveness analyses of digital support tools.…”
Section: Strengthsmentioning
confidence: 99%
“…The impact of ineffective communication during transitions of care (TOCs) on these outcomes was not assessed by these studies. There are ongoing clinical trials on economic impact and clinical outcomes of focused TOC interventions for patients with chronic pain to address this gap in the literature 25,26 . To fill the current void in standards, the Island Peer Review Organization (IPRO) Pain Management Coalition undertook an initiative to generate a consensus list of requisite communication elements (RCEs) that experts agree should be communicated between care settings during TOCs for all patients utilizing opioid analgesics.…”
mentioning
confidence: 99%